Perlindungan Konsumen Rokok Elektrik Ditinjau Dari Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan Dan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Siti Mutmainnah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThis study aims to determine how effective the implementation of legislation in protecting consumers of Electric Cigarettes reviewed from Law Number 36 Year 2009 on Health and Law No. 8 of 1999 on Consumer Protection. And how the efforts of Food and Drug Supervisory Agency (BPOM) and Health Office of Samarinda Protect Consumer E-Cigarette (E-Cigarette) This research was conducted in Samarinda City, East Kalimantan Provincial Health Office and East Kalimantan Food and Drug Administration (BPOM) Office By conducting interviews related to this research. In addition, the authors also interviewed with some elktronik cigarette seller and also conducted interviews to several Consumers Electronic Cigarettes. Based on the results of the discussion of the author, it can be concluded as follows: the application or effectiveness Law No. 36 of 2009 on Health and Law No. 8 of 1999 About Consumer Protection in practice has not been realized, whereas Electronic Cigarettes can be categorized as Tobacco Products because it has Meet the qualification of addictive substances. Effort of Health Service to protect consumer of Electronic Cigarette until now is only danger warning to use Electronic Cigarette to society by taking result of research sample which have done by State first doing research on Electronic Cigarette and Health Department have not conducted official research related to Electronic Cigarette so that not yet PP 109 Year 2012 as a rule of law that can be applied to Electronic Cigarettes, it takes legal efforts from the government regarding the existence of Electronic Cigarettes in the community, especially about what legal rules that can normatively be a legal umbrella for Electronic Cigarettes, this is to protect consumer rights in Indonesia. Health Office and Food and Beverage Supervisory Agency (BPOM) need to conduct an official research on Electronic Cigarettes,Keywords: Electric Cigarette Hazards, Regulatory Effectiveness